The influence of social capital and entrepreneurial attitude orientation on entrepreneurial intentions: The mediating role of psychological capital - Tuatul Mahfud; Mochamad Bruri Triyono; Putu Sudira; Yogiana Mulyani (European Research on Management and Business Economics (ERMBE), 2020)
The entrepreneurial intention plays a vital role in generating new business. Although many studies have shown that attitude is influential in shaping intentions, few discuss this relationship by engaging interactively with social and psychological capital. This study aimed to develop a structural model to form the entrepreneurial intention of polytechnic students which involves the interplay of entrepreneurial attitude orientation, social capital, and psychological capital. Data were collected randomly through an online questionnaire completed by 215 polytechnic students in Indonesia. Structural equation modelling analysis was used to examine the structure model of developing entrepreneurial intentions and bootstrap confidence intervals were estimated to test the mediating role. The results reveal that entrepreneurial attitude orientation, social capital, and psychological capital collaboratively and interactively influence the entrepreneurial intention of polytechnic students. Psychological capital was shown to have a positive partial mediation effect on the relationship between entrepreneurial attitude orientation and entrepreneurial intention. Finally, psychological capital was also found to fully mediate the impact of a social capital on entrepreneurial intention. The findings of this study are discussed and some proposals with implications for vocational education practitioners are provided.
Keywords: I23; L26; M13; 650; New business; Entrepreneurial intention; Social capital; Psychological capital